Glocal Religions: An Introduction - Roudometof, Victor (Religions, 2018)
This introductory article offers an overview of the volume's major problematic. It examines the literature on religion and globalization and then moves on to an overview of the literature on religion and glocalization. Throughout the discussion, the article refers explicitly to the volume's chapters and outlines how their specific themes fit within the broader problematic of glocal religions.